BEYOND EUROSCEPTISISM AND EURIPHILIA: MULTIPLE VIEWS ABOUT EUROPE - F. Russo; M. Cotta (Сравнительная политика)
The purpose of this paper is to map the structure of preferences concerning the European Union held by parliamentarians of the member states. The opinions of national politicians are relevant as they influence the governments which participate in the institutions and the decision making processes of the Union. Do they evaluate the European integration process according to a single independence-integration dimension? Or do they acknowledge the existence of multiple lines of conflict? Is the structure of preferences stable? Finally, how are national parliamentarians grouped according to their preferences and what this can tell about the future of European Integration? This paper, based on a two waves survey of national parliamentarians belonging to 16 member states, analyses their views about the “governance system” and the “policy goals” of the EU. The findings of this paper shed some new light on several old questions. Firstly, while several studies assume that the preferences about European Integration can be ordered in a one-dimensional continuum that has the “status quo” and “complete integration” as the two opposite poles, this paper shows that the preferences of national parliamentarians have a multi-dimensional structure. Secondly it moves to analyse the four main clusters of national parliamentarians which these preferences generate. And thirdly it discusses how these clusters react to different problems and challenges the EU faces today.